A comparative study of the minimum inhibitory and mutant prevention concentrations of florfenicol and oxytetracycline for animal isolates of Pasteurella multocida and Salmonella Typhimurium - Van Vuuren, Moritz (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2012.